Preschool educational program of preschool educational organization: rethinking the approach to design and implementation - Tatyana V. Krivtsova (Современное дошкольное образование)
Background. This problem is caused by two factors. On the one hand, there is a need to develop educational programs for various types of preschool educational organizations operating in the conditions of standardization of preschool education content. On the other hand, there is a lack of an approach that allows designing and implementing educational programs in accordance with the current norm.